The courtship behaviour of the pipefish Nerophis lumbriciformis: Reflections of an adaptation to intertidal life - Monteiro, Nuno Miguel (2012)
The courtship behaviour of Nerophis lumbriciformis (Pisces: Syngnathidae) consists of three distinct phases (initial courtship, spawning, and embrace) marked by prominent behavioural changes. The first courtship phase is characterised by female quivering. Courtship activity increases from low to high levels of quivering, causing undulatory head movements in the female. In the second phase, the female transfers her eggs onto the male incubating ventral surface. During the final phase, the male wraps his body around the female (embrace). Females actively initiate courtship indicating that these pipefishes are courtship role reversed. The complete lack of swimming and vertical movements in the courtship behaviour of N. lumbriciformis, unlike in the behaviour of other syngnathid species, suggests an adaptation to intertidal conditions.